'Classroom in the cloud': from virtual to social collaborative learning. (1st January 2013) - Smith, Jamie E.; Davies, Chris; Evans, Chris
Electronic learning is growing at an unprecedented rate requiring new approaches to the delivery of technology enabled learning. Global education leaders are facing increasingly diverse learners who expect to learn in a way, time and place that suits them and on a device of their choosing. To meet these challenges, Birmingham Metropolitan College (BMet) joined with global technology leader IBM to create a unique learning experience titled 'Classroom in the cloud'. Using IBM Smart Cloud technology and founded on an ambition to move from virtual learning environments to social collaborative learning spaces that create an eco-system, throughout 2012 BMet has been implementing this vision as it explores the possibilities for the reinvention of learning. This paper revises and expands where appropriate the paper entitled 'Classroom in the cloud' presented at the 1st International IBM Cloud Academy Conference (ICA CON 2012) on Thursday 19th April 2012 in North Carolina, USA.